2005
DOI: 10.3748/wjg.v11.i17.2626
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dosimetric factors of radiation-induced esophageal injury: Radiation-induced esophageal toxicity

Abstract: AIM:To analyze the clinical and dosimetric predictive factors for radiation-induced esophageal injury in patients with non-small-cell lung cancer (NSCLC) during threedimensional conformal radiotherapy (3D-CRT). METHODS:We retrospectively analyzed 208 consecutive patients (146 men and 62 women) with NSCLC treated with 3D-CRT. The median age of the patients was 64 years (range 35-87 years). The clinical and treatment parameters including gender, age, performance status, sequential chemotherapy, concurrent chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 16 publications
0
46
1
2
Order By: Relevance
“…They identified that simultaneous chemotherapy doubled the risk of AE (p=0.001). Others reported this rate as a 12-fold increase (Werner Wasik et al, 1999;Qiao et al, 2005;Caglar et al, 2010). In a series of 105 lung cancers, grade 3 AE was not seen in patients who received only RT; while the rate of grade 3 AE was reported to be 18% in the CRT group (p=0.001) (Werner Wasik et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They identified that simultaneous chemotherapy doubled the risk of AE (p=0.001). Others reported this rate as a 12-fold increase (Werner Wasik et al, 1999;Qiao et al, 2005;Caglar et al, 2010). In a series of 105 lung cancers, grade 3 AE was not seen in patients who received only RT; while the rate of grade 3 AE was reported to be 18% in the CRT group (p=0.001) (Werner Wasik et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…This value is reported as 55 Gy by Singh et al (2003) in their series of 207 cases from a Western society and 60 Gy by Qiao et al (2005) in their series of 208 cases comprising a Far Eastern society.…”
Section: 4223 Dosimetric and Clinical Predictors Of Acute Esophagitimentioning
confidence: 94%
“…For esophageal toxicity, we chose to look at D2cc as several series have shown maximum doses to the esophagus to predict grade 3 esophagitis. [22][23][24][25] Furthermore, using maximum dose reduces the impact of variations in esophageal contours. While esophageal contours were standardized in the UM cohort, there are likely variations in the MROQC database.…”
Section: Discussionmentioning
confidence: 99%
“…Olguların yalnızca %0.4-1'inde geç özefagus hasarına (örn. trakeoözefa-geal fistül, özefagus perforasyonu) bağlı ölüm bildirilmektedir (54,55 (57). Yüksek riskli olan hastalardaki bir diğer önemli nokta ise hayatı tehdit edebilecek olan komplikasyonların erken tanısı açısından klinisyenin uyanık olmasıdır.…”
Section: Radyoterapi Komplikasyonlarıunclassified